The Defense of Islam by Poets – Hassān ibn Thābit as a Model - Andam, Abdulsalam Mohamed Omar (Sharwes Scientific Journal, 2026)
Hassan ibn Thabit was known as the Poet of Islam, as he utilized his eloquence to defend Islam and its noble Messenger. He possessed remarkable linguistic talent, which he employed to respond to polytheists and their poets who ridiculed the Prophet ﷺ and the Muslims. His poetry was characterized by sophistication and profound eloquence, making it an effective weapon in verbal battles.   Through his verses, Hassan demonstrated his defense of the Prophet by highlighting his sublime attributes and noble lineage, while also introducing the values and moral principles of Islam, which far surpassed the ignorance of Quraysh. He attacked the enemies of Islam with satire, exposing their flaws and negative behavior.   Hassan’s poetry had a significant impact in boosting the morale of Muslims in the face of verbal attacks from polytheists. He transformed poetry into a powerful medium for spreading the message of Islam in an impactful manner. His defense of Islam continued until his passing, leaving behind a poetic legacy that serves as a model of art committed to noble values and faith in the cause.